Relation between partial melting, granulite metamorphism, crystallization, deformation of leucosome and the influence of these processes in the rheology of the lower continental crust - Hernandez Tasco, Lizeth (2020)
The main objective of this study is to contribute to the understanding of deformation of leucosome and its residue, in diatexites and granulites, using as examples two units of the Nappe Socorro-Guaxupé, the metatexite unit and the basal granulite unit, from the southernmost portion of the Brasília Orogen. The first is dominated by metasedimentary rocks, although has a name of metatexite unit, it is dominated by diatexite at its base, and the second, is composed primarily by felsic granulite. In oriented samples, after textural characterization, the quartz caxis fabric thermomether and cathodoluminescence (CL) images, where Ti in quartz evidences temperature domains, were used to determine the deformation temperature, which was compared with thermobarometry data in the respective residues. In this way, it was established that the crystallization in the basal granulite and metatexite units occurred along the cooling portion of the P-T path, but in some portions, it was deformed and might be related to medium and high temperatures. During the metamorphism of the amphibolite and granulite facies, synanatectic deformation with melt crystallization and late deformation in solid-state occurred. Therefore, when the granulite is in the solid state, the diatexite is still in the dominantly liquid state, causing the granulite to register those higher deformation temperatures that the diatexite cannot register due to its still mostly liquid state.